Protective effect of green tea against prostate cancer: A case-control study in southeast China - Jian, Le; Lee, Andy; Binns, Colin (John Wiley and Sons Inc, 2004)
To investigate whether green tea consumption has an etiological association with prostate cancer, a case-control study was conducted in Hangzhou, southeast China during 2001–2002. The cases were 130 incident patients with histologically confirmed adenocarcinoma of the prostate. The controls were 274 hospital inpatients without prostate cancer or any other malignant diseases, and matched to the age of cases. Information on duration, quantity and frequency of usual tea consumption, as well as the number of new batches brewed per day, were collected by face-to-face interview using a structured questionnaire. The risk of prostate cancer for tea consumption was assessed using multivariate logistic regression adjusting for age, locality, education, income, body mass index, physical activity, alcohol consumption, tobacco smoking, total fat intake, marital status, age at marriage, number of children, history of vasectomy and family history of prostate cancer. Among the cases, 55.4% were tea drinkers compared to 79.9% for the controls. Almost all the tea consumed was green tea. The prostate cancer risk declined with increasing frequency, duration and quantity of green tea consumption. The adjusted odds ratio (OR), relative to non-tea drinkers, were 0.28 (95% CI = 0.17–0.47) for tea drinking, 0.12 (95% CI = 0.06–0.26) for drinking tea over 40 years, 0.09 (95% CI = 0.04–0.21) for those consuming more than 1.5 kg of tea leaves yearly, and 0.27 (95% CI = 0.15–0.48) for those drinking more than 3 cups (1 litre) daily. The dose response relationships were also significant, suggesting that green tea is protective against prostate cancer.